2013
DOI: 10.1109/tcpmt.2012.2221090
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Growth of Intermetallics in an Annealing-Twinned Ag-8Au-3Pd Wire Bonding Package During Reliability Tests

Abstract: Wire bonding on Al pad packages with an innovative annealing twinned Ag-8Au-3Pd alloy wire results in a sufficient interfacial intermetallic layer at the initial as-bonded stage, while its growth during the further temperature cycling test and pressure cooker test is very slow. Even after prolonged high-temperature storage at 150°C for 500 h, the thickness of its intermetallics is only around 1.7 µm. In contrast, a very thin CuAl 2 intermetallic layer appears at the interface of the Pdcoated Cu wire bonded pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…A cluster of alloying Au and Pd elements was not observed, and these alloying elements were considered to be uniformly distributed even after the HTSTs. It was therefore suggested that the elemental addition of Au and Pd could increase the resistance to oxidation and sulfuration of the Ag bonding wire [19]. The alumina layer still remained after 2000 h, suggesting that the thermal energy during HTST at 150 and 175°C did not affect it, even though the IMC was grown by atomic inter-diffusion through or beside the alumina layer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A cluster of alloying Au and Pd elements was not observed, and these alloying elements were considered to be uniformly distributed even after the HTSTs. It was therefore suggested that the elemental addition of Au and Pd could increase the resistance to oxidation and sulfuration of the Ag bonding wire [19]. The alumina layer still remained after 2000 h, suggesting that the thermal energy during HTST at 150 and 175°C did not affect it, even though the IMC was grown by atomic inter-diffusion through or beside the alumina layer.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a variety of Ag alloys have been designed for better bonding wire and improved properties. Additionally, the Ag-Al bond reliability has been evaluated [14][15][16][17][18][19]. Technologies based on Pd coatings and the addition of Ag bonding wire have been introduced, which improve the efficiency of the fabrication process and the Ag-Al bond reliability [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Ag-Al IMC phases reported are not conclusive. One research group indicated Ag 4 Al and Ag 2 Al phases [18] and others showed AgAl 2 , Ag 2 Al and Ag 3 Al phases at the Ag/Al interface [19,20]. Moreover, although many studies have reported the reliability test results of the Ag-Al wire bonds [18][19][20][21], the mechanical properties of the Ag-Al intermetallics are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies regarding the Ag wire as compared to Au and Cu [4][5][6][7][8][9][10]. Cho et al [4] reported that Pd alloying of the Ag wire was effective in improving the reliability of Ag ball bond.…”
Section: Introduction (Heading 1)mentioning
confidence: 99%